Neural correlates of audiovisual integration in schizophrenia – an ERP study - Borgolte, A.; Sinke, C.; Michalke, L.; Möde, L.; Lepsy, N.; Wiswede, D.; Bleich, S.; Szycik, G. R.; Ghaneirad, E. (Frontiers in Psychiatry, 2024)
IntroductionMultisensory integration (MSI) enhances perception by combining information from different sensory modalities. In schizophrenia, individuals often exhibit impaired audiovisual processing, resulting in broader temporal binding windows (TBWs) which appear to be associated with symptom severity. Since the underlying mechanisms of these aberrations are not yet fully understood, the present study aims to investigate multisensory processing in schizophrenia in more detail.MethodsIndividuals with schizophrenia (SZ) and healthy controls (HC) performed a simultaneity judgement task, a paradigm that is suitable for the examination of multisensory integration processes. The paradigm was also conducted to allow for the comparison of perceptions under ecologically valid and invalid conditions. Additionally, EEG recordings were made to explore underlying neural mechanisms.ResultsIn line with previous research, we replicated enlarged TBWs in SZ compared to HC, independent of ecological validity. Neurophysiological data further revealed reduced amplitudes in the early ERP complex N1/P2 in SZ compared to HC.DiscussionSince amplitude reduction in the N1/P2 complex is often associated with audiovisual integration processes, the results highlight perceptual dysfunction in SZ, particularly concerning the disengagement of auditory and visual stimuli.